Z formal specification of functional requirement / Nursyahidah Alias, Mohd Norafizal Abd Aziz and Zazaleena Zakariah - Nursyahidah Alias; Mohd Norafizal Abd Aziz; Zazaleena Zakariah (Research Management Institute (RMI), 2013)
Formal approach will remove ambiguity in the specification. Formal specification is used to highlight an error in a specification. A developer of a system can detect an error of the system in early phase of system development life cycle. A verification and validation activity can be reduced towards the end of the lifecycle. It is about getting more things right earlier in the software lifecycle. A system developed by a student cannot be used because the user detects a misflow of functional requirement in the system. The user explained to the developer about the misflow using natural language, but natural languages are ambiguous and lead to misinterpretation. The study is to develop a specification for E-pracCs system using formal approach. The formal specification for the system uses Z formal specification language.